Effect of adding brush on the bottom of the ice-valve-sealed pressure-retaining device on ice formation speed. (5th February 2021) - Lian, Moke; Peng, Jianming; Huang, Chaoyang; Li, Yanliang; Zhang, Guang
Highlights: Using porous media to substitute brush to explore their impact on Natural Convection. The numerical simulation analysis was carried out and verified by experiments. The temperature distribution of liquid in ice valve tube under different porosity conditions is discussed. Abstract: The ice-seal holding-pressure technology has attracted more and more attention for it does not have the disadvantages of traditional mechanical seals, therefore, its applications are more and more extensive. To make better use of the ice valve, the influence of setting different porosity on the formation rate of the ice valve and the optimization of its pressure-holding performance was discussed. The creative point is to use a brush as the blocking medium to obstruct the natural convection, the calculation parameters of the brush were set at the bottom of the ice valve tube by the porous media model in CFD software Fluent to investigate the different laws of ice valve formation under different porosity conditions, and compare the calculation results with laboratory test results. The results show that with the decrease of the fluid porosity at the bottom of the ice valve tube, the natural convection strength and the loss of cooling capacity are correspondingly reduced, and the formation time is consistent with the laboratory test. The ice valve will be formed in the porous medium area in advance, which could further reduce the formation time of the ice valve 5–7 min, and avoid the unfrozen situation at the center of the ice valve tube after a long time under no-brush condition.